The Effectiveness Of The Discoveri Learning Model Of Students' Ability To Understand Mathematical Concepts - Asri A. Muliana, Kristayulita, Mauliddin (Lembaga Bale Literasi, 2021)
Therefore the purpose of this study is to determine the effectiveness of a learning model that is guided learning model (Discovery Learning) on ​​the ability to understand students' mathematical concepts. This research was conducted at MTs. Miftahul Ma'arif Pelambik which takes place from February to March 2020. The subject of this research is class VII MTs. Miftahul Ma'arif, the sample used was class VII B as a control class and class VII A as an experimental class. The instrument used in this study was the Learning Implementation Plan (RPP) with the Discovery Learning learning model and written test in the form of a description of the material with the set and the form of algebra. This research is a quantitative type of experimental research, while the form is The Non Equivalent Conrol Group Design. Data analysis using t test using the formula of separated variance t test results showed t_count> t_table namely 5.15> 3.17 then H_0 was rejected. Thus the results of this study are effective discovery learning models (Discovery Learning) on ​​the ability of understanding MTs students' mathematical concepts. Miftahul Ma’arif.